Pengembangan Potensi Diri Kelompok Sadar Wisata di Desa Wanurejo Magelang pada Masa New Normal - Sri Oemiati; Rahmanti Asmarani; Emik Rahayu (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
Borobudur is one of the tourist attractions in Central Java. It is a great destination for the tourists, both local and foreign tourists. The villages around the Borobudur temple also have the potential attractions for tourists, such as Wanurejo village and Candirejo village. Those have been designated as tourist villages. As the tourist villages, or the “Pokdarwis” they continuously try to improve their professionalism. The awareness to entertain tourists, especially foreign tourists, requires not only language skills, but also the ability to understand the culture of the tourists. They also try to establish cooperation with outside parties who can assist them in understanding the foreign language and culture.This mentoring activity is expected to improve the professionalism of the community, especially for the “Pokdarwis” in Wanurejo and Candirejo villages in recognizing and understanding foreign languages and cultures.